HOW EFFECTIVE IS THE USE OF THINK PAIR SHARE STRATEGY IN IMPROVING SECONDARY HIGH SCHOOL STUDENTS SPEAKING PERFORMANCE? - Pajrina, Elin; Amalia, Shynta; Jannah, Siti Raudhatul (English Language Education Program, Faculty of Education and Teacher Training, Sulthan Thaha Saifuddin State Islamic University of Jambi, 2022)
The objective of this study is to determine whether the Think-Pair-Share (TPS) technique can significantly improve students' speaking abilities. The researcher employed a quasi-experimental study design with a pre- and post-testing control group. This study included participation from forty students. Twenty students were assigned to the experimental group, while the remaining 20 were assigned to the control group. The result of the pair sample t-test indicates that there was a statistically significant improvement in the speaking performance of students before and after the adoption of the Think-Pair-Share approach (M = 11.98, T = -8.839), P 0.05. The overall findings of the study indicate that the Think-Pair-Share technique can improve the performance of the students. In addition, Think- Pair-Share provided the students with extra opportunities to communicate English. The students‟ English speaking confidence increased. They also contributed actively to the teaching and learning process.